KEBERADAAN DAN PERKEMBANGAN PEKERJA SEKS KOMERSIAL (PSK) DI TANJUNG BALAI KARIMUN TAHUN 2000-2014 (Suatu Tinjauan Sejarah Sosial) - Emily Br. Hasibuan; Bedriati Ibrahim; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Commercial sex workers are women who work to sell herself to a lot of men who need gratification of sexual desire, and the woman received a sum of money in return, and shall be held outside of marriage. This study aims to determine the entry of commercial sex workers in Tanjung Balai Karimun, the cause of the persistence of commercial sex workers in Tanjung Balai Karimun, community feedback about commercial sex workers to the existence and development, and the impact of the presence of commercial sex workers in the economy, culture, and education local communities in Tanjung Balai Karimun. This research used a descriptive research method because in practice, such as data, analysis and interpretation of the meaning and the data obtained. Data were collected through interviews and questionnaire techniques. These results indicate that the presence of commercial sex workers in Tanjung Balai Karimun still survive but not growing. The impact of commercial sex workers have an effect on all areas, whether economic, cultural, and educational. The persistence of commercial sex workers in Tanjung Balai Karimun due to several factors, both internal and eksteren. Until finally the people who feel the impact.Keywords: existence, development, commercial sex workers, History, Social.